Productivity, structural change, and Latin American development - Carlos Machicado; Felix Rioja; Antonio Saravia (Institute for Advanced Development Studies (INESAD), 2012)
We calibrate a simple neoclassical model of structural transformation to a set of Latin American countries and show that slow growth in agricultural productivity can substantially delay the development process and result in signi cant di erences in per capita incomes. Some of our results indicate that low agricultural productivity delayed the beginning of the industrialization process in Paraguay and Bolivia by about 100 years compared to the leader of the group, Chile. The development pro- cess can be accelerated, however, by increasing productivity in the non-agricultural sector. In fact, in the long run, it is non-agricultural productivity what determines the speed of convergence. Improvements in non-agricultural productivity between 20% to over 100% would be required for the other Latin American countries in our set to signi cantly close the income gap with Chile by the end of the century.
Keywords: O47; O57; E13; 330; Economic Development; Latin America; Agriculture Productivity; Manufacturing Productivity; Entwicklung; Produktivität; Strukturwandel; Neoklassik; Lateinamerika